Forensic Assessment of Tramadol Detection: Comparative Analysis of Drug Persistence in Albino Rat Hair Follicles and Serum Samples - H.M, Chiwar; F.A, Chiroma; M.A, Fugu; I.A., Agyigra; A. I., Musa; M. N., Shuaibu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Drug abuse presents significant challenges to public health and safety, necessitating effective methods for detecting and monitoring. Tramadol, a widely used opioid analgesic, has garnered attention due to its abuse potential. Traditional methods of drug detection, such as serum analysis, may not capture long-term exposure patterns effectively. This study aims to assess the feasibility of using hair follicles as an alternative matrix for detecting tramadol exposure and to compare the detection window of tramadol in hair with traditional serum samples. Thirty-two albino rats were divided into low and high dose groups and exposed to tramadol orally for seven days, while control groups received water. After euthanasia at various intervals post-exposure, blood and hair samples were collected and analyzed for tramadol concentration using spectrophotometric method. Results revealed that Serum tramadol levels declined rapidly attaining undetectable concentration after one week post-exposure, while tramadol concentrations in hair persisted for an extended period, up to the study endpoint with significant detectable concentration even after one month. The low dose group exhibited detectable tramadol concentrations across all time points post-exposure, while the high dose group showed higher initial concentrations, gradually decreasing over time. In conclusion, the study highlighted that serum analysis is suitable for detecting recent tramadol ingestion, whereas hair analysis offers a retrospective assessment of drug exposure over longer periods. These findings highlight the complementary nature of serum and hair analyses in tramadol toxicology assessments, providing insights into drug use patterns beyond the acute phase.